Are grandparents raising grandchildren receiving the services they need? - Karleah Harris; Gifty Ashirifi; Charlene Harris; Jonathan Trauth (Journal of Childhood, Education & Society, 2021)
Grandparents play an important role in the upbringing of grandchildren and face increased levels of stress. Using family stress theory, the present study examined the effectiveness of service programs for grandparents raising grandchildren. Data were collected through focus group interviews and audiotaped from a sample of four custodial grandparents living in Ohio U.S.A. To better understand grandparents that are raising their grandchildren, we asked the following questions: 1) What support is needed for grandparents raising grandchildren? 2) At what stage is the support needed: beginning, middle or late stages of caregiving? 3) What are grandparent caregivers’ perceptions of service programs? The audiotape was transcribed verbatim and analyzed for themes relevant to the research questions. The findings from these questions are examined and implications discussed.